Pengenalan Teknologi Sederhana Pengolahan Saus Berbasis Pangan Lokal pada Anggota ‘Aisyiyah Kota Semarang - Siti Aminah; Wikanastri Hersoelistyorini; Nurrahman Nurrahman (Universitas Muhammadiyah Semarang, 2021)
Sauce and chili sauce are pasta product that well-known and popular in the community. These products can be processed through simple technology at the household level. Local food ingredients such as papaya, pumpkin, and chayote can be used as raw material for sauces. Not many people know about the appropriate technology for processing sauces with local ingredients. This activity aims to introduce appropriate technology for processing sauces and chili sauce with local ingredients. The method of implementing activities was through training includes lectures for theoretical material on food safety, food additives and packaging. While the introduction of appropriate technology was carried out by practicum. For carrying out practicum, participants were divided into groups (5 people / group). The target of this activity is 50 members of 'Aisyiyah Semarang City. In general, the results of the activities showed that the target participants were 50 people, and all of them followed a series of activities until the end. The participation and activeness of all participants in lectures and practicum showed that this service activity has been achieved. The results of the practicum in the form of sauce and chili sauce products generally had fairly good characteristics. This shows that the appropriate technology for processing sauces and chili sauce with diversification of local food ingredients can be understood and implemented properly by all participants. This activity has been able to provide new information to participants in addition to the processing process as well as the utilization of local materials that have not been known to the participants beforehand.